Analisis Literasi Keuangan, Perilaku Keuangan, Dan Pendapatan Terhadap Keputusan Investasi - Ulfy Safryani; Alfida Aziz; Nunuk Triwahyuningtyas (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Research is a quantitative study that has a purpose to know the influence of financial literacy, financial behaviour and income to investment decisions. The population in this research is the permanent lecturer Faculty of Economics and Business of National Development University Veteran Jakarta. Samples were taken as many as 80 respondents, with non probability sampling methods, purposive sampling. Data collection is done by spreading the questionnaire to the sample that has been determined through Google form. Data analysis techniques used are analysis methods PLS (Partial Least Square) with Smart software PLS 3.0. The results of this study show that: (1) Financial literacy has an influence on investment decisions with the value of the line coefficient of 0.455; (2) Financial behavior has no influence on investment decisions with the value of the line coefficient 0.165; (3) Revenue has an influence on investment decisions with a line coefficient value of 0.337. Keywords: Financial Literacy; Financial Behavior; Income; Investment Decisions